2015
DOI: 10.1002/hed.24108
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quality of life between open and endoscopic thyroidectomy for papillary thyroid cancer

Abstract: Current findings suggest that endoscopic thyroidectomy may offer more rapid recovery of emotional and physical function than open thyroidectomy. © 2015 Wiley Periodicals, Inc. Head Neck 38: E827-E831, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…Furthermore, there was a high level of heterogeneity among the studies ( I 2 =80%, P <0.00001). After excluding the study by Lee et al,33 there were still no significant differences between groups (WMD −0.14, 95% CI −0.47 to 0.20, P =0.42), but no heterogeneity was observed among the studies ( I 2 =0%).…”
Section: Resultsmentioning
confidence: 77%
“…Furthermore, there was a high level of heterogeneity among the studies ( I 2 =80%, P <0.00001). After excluding the study by Lee et al,33 there were still no significant differences between groups (WMD −0.14, 95% CI −0.47 to 0.20, P =0.42), but no heterogeneity was observed among the studies ( I 2 =0%).…”
Section: Resultsmentioning
confidence: 77%
“…A comparative study also reported the benefits of endoscopic thyroidectomy during the early postoperative period. Lee et al demonstrated early improvement in physical and emotional functions in patients who underwent transaxillary endoscopic thyroidectomy compared with those who underwent conventional open thyroidectomy [ 18 ]. Despite a higher pain score, endoscopic thyroidectomy may be an alternative for patients who value a better quality of life and better cosmetic result.…”
Section: Discussionmentioning
confidence: 99%
“…Successful thyroidectomy surgery and radioiodine treatment can return patients to a HRQoL that approximates the average EQ-5D of the UK general population (0.856 mean for the UK population [59]) although, while receiving thyroid cancer treatment, HRQoL is negatively impacted [20,21,26,27,49].…”
Section: Discussionmentioning
confidence: 99%